Favorable outcome after single-kidney transplantation from small donors in children: a match-controlled CERTAIN registry study - Schild, Raphael-Sebastian; Carvajal Abreu, Karla; Büscher, Anja; Kanzelmeyer, Nele; Lezius, Susanne; Krupka, Kai; Weitz, Marcus; Prytula, Agnieszka; Printza, Nikoleta; Berta, László; Saygili, Seha Kamil; Sellier-Leclerc, Anne-Laure; et al. (Transplantation, 2024)
Background. - Kidney transplantation (KTx) from small donors is associated with inferior graft survival in registry studies, whereas single-center studies show favorable results. - Methods. - We compared 175 pediatric KTx from small donors ≤20 kg (SDKTx) with 170 age-matched recipients from adult donors (ADKTx) from 20 centers within the Cooperative European Paediatric Renal Transplant Initiative registry. Graft survival and estimated glomerular filtration rate (eGFR) were analyzed by Cox regression and mixed models. Detailed data on surgical and medical management were tested for association with graft survival. - Results. - One-year graft survival was lower after SDKTx compared with ADKTx (90.9% versus 96.5%; odds ratio of graft loss, 2.92; 95% confidence interval [CI], 1.10-7.80; P = 0.032), but 5-y graft survival was comparable (90.9% versus 92.7%; adjusted hazard ratio of graft loss 1.9; 95% CI, 0.85-4.25; P = 0.119). SDKTx recipients had an annual eGFR increase of 8.7 ± 6.2 mL/min/1.73 m² compared with a decrease of 6.9 ± 5.7 mL/min/1.73 m² in ADKTx recipients resulting in a superior 5-y eGFR (80.5 ± 25.5 in SDKTx versus 65.7 ± 23.1 mL/min/1.73 m² in ADKTx; P = 0.008). At 3 y posttransplant, eGFR after single SDKTx was lower than after en bloc SDKTx (86.6 ± 20.4 versus 104.6 ± 35.9; P = 0.043) but superior to ADKTx (68.1 ± 23.9 mL/min/1.73 m²). Single-kidney SDKTx recipients had a lower rate of hypertension at 3 y than ADKTx recipients (40.0% versus 64.7%; P = 0.008). - Conclusions. - Compared with ADKTx, 5-y graft function is superior in SDKTx and graft survival is similar, even when performed as single KTx. Utilizing small donor organs, preferably as single kidneys in experienced centers, is a viable option to increase the donor pool for pediatric recipients.